Factors Associated with Gadget Addiction in Children at Inpres III Elementary School Perumnas Antang Makassar City - Sri Rahmah Haruna; Suci Rahmadani; Nur Afni Ponseng; Herti Haerani; Safira Senggo’ Palayukan (Lambung Mangkurat University, 2022)
During the pandemic until the start of the COVID-19 endemic period, the government made a policy to do activities at home including studying online. These conditions make children's activities preoccupied with gadgets every day, so it is feared that it can lead to addiction. The research objective was to determine the factors associated with gadget addiction in school-age children at Inpres III Elementary School Perumnas Antang, Makassar City. This study used quantitative research using a cross-sectional approach. The research was conducted in August 2022. Sampling used an accidental sampling technique. The study conducted at Inpres III Elementary School Perumnas Antang Makassar City had a total sample of 132 respondents. As for the variables used for gadget addiction in school-age children, the results obtained were internal factors p-value = 0.000, external factors p-value = 0.000, situational factors addicted p-value = 0.000, social factors p-value = 0.000, and demographic factors p-value = 0.000. There is a relationship between internal factors, external factors, situational factors, social factors, and demographic factors on gadget addiction in school-age children at Inpres III Elementary School Perumnas Antang, Makassar City